Media audience research a guide for professionals - Mytton, Graham; Diem, Peter 1937-; Dam, Piet Hein van 1967- (SAGE Publications, Inc., 2016)
The only comprehensive training book on conducting research into all forms of media This book outlines all the methods for conducting research-both active and passive as well as quantitative and qualitative-in all forms of media, including new media such as the Internet, mobile phones and social media. It explains the ways in which media audiences are measured, understood and taken into account in media planning, advertising sales and social development campaigns. It shows how datasets are analysed and used. The statistical theories behind good quantitative research are explained in simple and accessible language